Characteristics and treatment outcomes of newly diagnosed epilepsy in older people: A 30‐year longitudinal cohort study. (23rd October 2020) - Alsfouk, Bshra Ali A.; Hakeem, Haris; Chen, Zhibin; Walters, Matthew; Brodie, Martin J.; Kwan, Patrick
Abstract: Objectives: To describe the clinical characteristics and evaluate the long‐term treatment outcomes in older people with newly diagnosed epilepsy over the past 30 years. Methods: We included patients newly diagnosed with epilepsy and commenced on antiseizure medications (ASMs) at age 65 years or older between July 1982 and October 2012 at the Western infirmary in Glasgow, Scotland. They were followed up until April 2016 or death. Seizure freedom was defined as no seizure for at least 1 year on unchanged medication at the last follow‐up. Results: A total of 201 patients (median age 73 years, 59% male) were included. The median duration from initial seizure to starting treatment was 8 months (interquartile range: 3.0‐24.0 months); 42.2% (85/201) patients had more than five seizures before commencing treatment. Brain imaging showed potentially epileptogenic lesions in 19.7% (38/193) of patients and other abnormalities in 56.5% (109/193); 78.6% patients (158/201) were seizure‐free at the last follow‐up, of whom 94.9% were taking monotherapy. Concomitant aspirin use (n = 80) was associated with a lower probability of being seizure‐free (relative risk 0.82, 95% confidence interval 0.70‐0.97; P  = .02). The use of second‐generation ASMs as the initial monotherapy increased from 31.5% (23/73) before 2000 to 70.3% (90/128, P  < .001) from 2000 onward. However, the seizure freedom rates (67.1% vs 55.5%; P  = .35) and intolerable adverse‐effect rates (16.4% vs 19.5%; P  = .45) did not show any significant difference. Significance: There was often a long interval between seizure onset and the initiation of treatment in older people with new‐onset epilepsy, although the majority responded well to ASM treatment. Brain imaging showed a high rate of abnormalities. Despite the increased use of second‐generation ASMs, treatment outcomes in later‐onset epilepsy have not improved over time. The possible effect of aspirin on treatment response warrants further investigation.